PENGARUH PEMBELAJARAN VIDEO IMERSIF INTERAKTIF TERHADAP MOTIVASI MURID DALAM PEMBELAJARAN PJOK DI SEKOLAH DASAR - Anjasmoro, Daud; Wibowo, Sapto; Priambodo, Anung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Motivation is closely related to the level of student learning engagement, focus, and success in school. In this study, the researcher used a quasi-experimental quantitative design. This study used a pretest-posttest control-group design involving 5th-grade students from Ketajen 1 Public Elementary School in Sidoarjo Regency. The researcher collected data using a learning motivation questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, the homogeneity test, the paired-samples t-test, and the independent-samples t-test. The normality test showed a p-value greater than 0.05, which means the data were normally distributed. The homogeneity test produced a p-value of 0.375 (above 0.05), which indicates that the data are homogeneous. The paired-samples t-test showed a significance value (2-tailed) of 0.000 for both groups, less than 0.05, indicating a difference between the pretest and posttest results in the experimental and control groups. The independent t-test also showed a significance value (2-tailed) of 0.000 (less than 0.05), indicating that learning using immersive video had a significant impact. In conclusion, learning Physical Education (PJOK) using immersive video can significantly increase student learning motivation.